(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Patients with chronic kidney disease undergoing percutaneous coronary intervention are at increased risk of contrast-associated acute kidney injury and adverse cardiovascular events. Intravascular ultrasound guidance may improve procedural optimization and reduce contrast exposure compared with conventional angiography-guided PCI. Methods: This prospective comparative study included 158 patients with chronic kidney disease and significant coronary artery disease requiring PCI. Patients were divided into two groups: IVUS-guided PCI group (n=79) and angiography-guided PCI group (n=79). Baseline demographic, clinical, renal, cardiac, angiographic, procedural, and follow-up outcome data were recorded. The primary outcome was contrast-associated acute kidney injury, defined as an absolute rise in serum creatinine of ≥0.3 mg/dL or a relative increase of ≥50% from baseline within 48–72 hours after contrast exposure. Secondary outcomes included contrast volume, procedural success, worsening renal function, need for dialysis, length of hospital stay, and major adverse cardiac events. Results: Baseline demographic, renal, cardiac, and angiographic characteristics were comparable between the two groups. The mean contrast volume was significantly lower in the IVUS-guided PCI group compared with the angiography-guided PCI group (72.4 ± 22.6 mL vs 108.7 ± 31.5 mL; p<0.001). The incidence of contrast-associated acute kidney injury was significantly lower in the IVUS-guided PCI group (5.1% vs 15.2%; p=0.034). Worsening renal function was also lower in the IVUS-guided group (7.6% vs 19.0%; p=0.035), and hospital stay was shorter (4.2 ± 1.4 days vs 5.1 ± 2.0 days; p=0.001). Follow-up major adverse cardiac events were significantly lower in the IVUS-guided group compared with the angiography-guided group (6.3% vs 17.7%; p=0.028). Conclusion: IVUS-guided PCI was associated with lower contrast use, reduced contrast-associated acute kidney injury, better renal outcomes, shorter hospital stay, and lower follow-up major adverse cardiac events compared with angiography-guided PCI in patients with chronic kidney disease. IVUS-guided PCI may be considered a safer and more effective revascularization strategy in CKD patients, particularly in those at high risk of contrast-related renal injury.